2020
DOI: 10.1097/qai.0000000000002224
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of HIV Status Is Associated With a Decrease in the Severity of Depressive Symptoms Among Female Sex Workers in Uganda and Zambia

Abstract: When I launched the 90-90-90 targets three years ago, many people thought they were impossible to reach. Today, the story is very different. Families, communities, cities and countries have witnessed a transformation, with access to HIV treatment accelerating in the past three years. A record 19.5 million people are accessing antiretroviral therapy, and for the first time more than half of all people living with HIV are on treatment. More countries are paying for HIV treatment themselves. More people living wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 85 publications
4
26
0
Order By: Relevance
“…Forty-four studies examined depression among FSWs, with 37 reporting prevalence estimates ( Table 1 ) [ 9 , 10 , 23 , 27 , 32 37 , 39 , 43 69 ]. A meta-analysis was conducted with 23 studies ( Fig 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Forty-four studies examined depression among FSWs, with 37 reporting prevalence estimates ( Table 1 ) [ 9 , 10 , 23 , 27 , 32 37 , 39 , 43 69 ]. A meta-analysis was conducted with 23 studies ( Fig 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen studies reported on suicidal ideation [ 10 , 36 , 39 , 46 , 47 , 55 , 57 , 58 , 61 , 69 , 71 , 75 80 ]. Most assessed suicidal ideation by asking about suicidal thoughts, for example, “have you thought about killing yourself?” and “have you ever felt like you wanted to end your life?” For the meta-analysis, we divided studies based on timeframe into ‘recent’ or ‘ever’ suicidal ideation and removed 3 studies due to limitations in how questions were operationalized [ 46 , 47 ], including one study that combined suicidal thoughts with attempting suicide [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings are largely consistent with HIVST research in Uganda. Quantitative research with the same cohort of FSWs found that learning one's HIV status led to decreases in the severity of depressive symptoms (Ortblad et al, 2020) and knowledge of an HIVnegative status led to increases in condom use (Ortblad et al, 2019), both factors that may be at least partially explained by the qualitative data showing that HIVST sparked feelings of self-worth, and a desire to live healthy, full lives (Wachinger et al, 2020). A qualitative study among FSWs in Rakai, Uganda, which preempted the distribution of HIVST kits, found that FSWs perceived HIVST as advantageous because it bolsters privacy and convenience, but problematic because it circumvents formal counseling, which is echoed in our data stemming from actual experience (Burke et al, 2017).…”
Section: Discussionmentioning
confidence: 99%